Y.M.C.A. Port of Spain Branch, Trinidad, B.W.I. - (:unkn) unknown (James Book Store, 2010)
Photo of the Y.M.C.A. Port of Spain Branch Building showing the front of the building. The windows and entrance are surrounded by arches. There are two women walking through the entrance and there is a bicycle parked on the side of the back entrance.
Colour: Black and White; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Buildings--Trinidad and Tobago; Architecture--Trinidad and Tobago; Y.M.C.A.; Young Men's Christian Association